Synthesis and anti-HCV activity of β-d-2′-deoxy-2′-α-chloro-2′-β-fluoro and β-d-2′-deoxy-2′-α-bromo-2′-β-fluoro nucleosides and their phosphoramidate prodrugs. Issue 4 (15th February 2019) - Ovadia, Reuben; Khalil, Ahmed; Li, Hao; De Schutter, Coralie; Mengshetti, Seema; Zhou, Shaoman; Bassit, Leda; Coats, Steven J.; Amblard, Franck; Schinazi, Raymond F.
Graphical abstract: Abstract: We report herein the synthesis and evaluation of a series of β-d -2′-deoxy-2′-α-chloro-2′-β-fluoro and β-d -2′-deoxy-2′-α-bromo-2′-β-fluoro nucleosides along with their corresponding phosphoramidate prodrugs. Key intermediates, lactols 11 and 12, were obtained by a diastereoselective fluorination of protected 2-deoxy-2-chloro/bromo-ribonolactones 7 and 8 . All synthesized nucleosides and prodrugs were evaluated with a hepatitis C virus (HCV) subgenomic replicon system.